Gambaran klinis dan karakteristik Hipomineralisasi molar-insisif: tinjauan pustaka - Yeini; Dian Rahmadini, Enrita; Dwimega, Arianne (Fakultas Kedokteran Gigi Universitas Trisakti, 2025)
Background: Molar-incisor hypomineralization (MIH) is a qualitative developmental enamel defect affecting one or more first permanent molars, with or without involvement of permanent incisors. MIH has emerged as a significant global oral health concern due to its high and increasing prevalence, wide variation across regions, and substantial clinical impact and quality of life on affected children. Objectives: This literature review aims to comprehensively discuss MIH, including its definition, epidemiology, clinical characteristics, etiology, diagnostic criteria, differential diagnosis, and associated clinical problems. Results: The reviewed literature demonstrates that the prevalence of MIH ranges widely worldwide, influenced by differences in diagnostic indices, examination protocols, and age groups studied. Clinically, MIH is characterized by demarcated opacities, enamel porosity, post-eruptive enamel breakdown, hypersensitivity, and atypical restorations, which predispose affected teeth to rapid caries progression and repeated dental interventions. The etiology of MIH is considered multifactorial, involving prenatal, perinatal, and postnatal factors; however, definitive causal mechanisms remain unclear. Accurate diagnosis relies on standardized criteria, particularly those recommended by the European Academy of Paediatric Dentistry, to ensure consistency in identification and reporting. Given the functional, esthetic, and psychosocial consequences of MIH, early detection and appropriate management are essential. Conclusion: This review highlights the importance of improving fundamental knowledge among dental practitioners to facilitate timely diagnosis and early intervention, thereby reducing disease severity and contributing to the prevention of increasing MIH prevalence.